2019
DOI: 10.1080/1359432x.2019.1630480
|View full text |Cite
|
Sign up to set email alerts
|

Epilogue: Frontiers in person–environment fit research

Abstract: In this editorial, that accompanies this special issue "Experiencing fit and misfit: Process views, dynamic interactions and temporal considerations", the guest editorial team reflects on the pressing issues and new research directions that emanated from our reading of the papers, our interactions with the authors and reviewers, and (in)formal discussions that were held with them and others in the lead up to this special issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…Past studies confirmed that multitasking may improve individuals' organizational commitment and job satisfaction, but these variables could not directly explain how polychronicity affects individual performance. Although polychronicity may enhance organizational commitment, past research works pointed out that the impact of organizational commitment on job performance could be mixed, weak, or even negative [2,3,9,10]. Therefore, certain mediations between polychronicity and job performance in this were considered in this study; in other words, after individual fit with a work situation, this relationship would affect the individual's mental state to further influence job performance.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Past studies confirmed that multitasking may improve individuals' organizational commitment and job satisfaction, but these variables could not directly explain how polychronicity affects individual performance. Although polychronicity may enhance organizational commitment, past research works pointed out that the impact of organizational commitment on job performance could be mixed, weak, or even negative [2,3,9,10]. Therefore, certain mediations between polychronicity and job performance in this were considered in this study; in other words, after individual fit with a work situation, this relationship would affect the individual's mental state to further influence job performance.…”
Section: Introductionmentioning
confidence: 97%
“…Previous research indicated that individual preference regarding time management is affected by organizational culture, personal experience, and the work environment, further influencing work attitudes, behaviors, and performance [1][2][3][4]. The modern workplace has gradually approached a multitasking philosophy [4,5], requiring employees to deal with several tasks simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars have concentrated latterly on expanding the model to include conceptualizations and reflection on the person‐environment fit (cf. Van Vianen, 2018; De Cooman et al, 2019; Weller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%